Political Sociology Analysis in The Scope of Students - Jagad Aditya Dewantara; Syamsuri Syamsuri; Jumarni Jumarni; Dilla Tri Aprillia; Afandi Afandi; Eka Safitri; Endang Maya Pratiwi; T Heru Nurgiansah (Universitas of Muhammadiyah Makassar, 2022)
Students are one of the smallest groups in society that have a role in the life of campus political sociology. So, students' awareness of their role as agents of change can provide a change in a social building for the better. The purpose of this research is to socialize in creating student awareness to participate in campus life. The method used is through observation and the author's experience in participating in campus organizations that have been followed. The method used through the author's observation and experience in following the campus organization that has been followed. The research method used is a qualitative approach. The results showed that students can play an active role in campus political activities. The conclusion of this study shows that many campus political activities are carried out by students.